An Algorithmic Solution for Adaptable Real-Time Applications - Khaluf, Lial; Rammig, Franz-Josef (the International Journal On Advances in Software)

Zirkel und Lineal ohne Parallelenaxiom: Ein konstruktiver Zugang zur hyperbolischen Geometrie. - Hoffmann, Max (Der Mathematikunterricht)

Die Bedeutung unterschiedlicher Heterogenitätsmerkmale für das Erleben von Zustandsangst vor dem Sportunterricht in der Grundschule - Grimminger-Seidensticker, Elke; Möhwald, Aiko Julia; Korte, J. (Grundschulsport. Empirische Einblicke und pädagogische Empfehlungen)

Von Interkultureller Kompetenz und sportpädagogischem Können in postmigrantischen Gesellschaften. Grundlagen und Weiterentwicklung eines Forschungsprogramms - Grimminger-Seidensticker, Elke; Gieß-Stüber, P.; Möhwald, Aiko Julia (Sport im Kontext globaler Zusammenarbeit)

Sportdidaktik - Grimminger-Seidensticker, Elke; Oesterhelt, V.; Gerlach, E.; Friedrich, G. (Lernen im Fach und über das Fach hinaus)

Zum Umgang mit Heterogenität im Sportunterricht - Grimminger-Seidensticker, Elke; Frohn, J. (Empirie des Schulsports)

Machthandlungen von Schüler*innen im Sportunterricht – Welche Rolle spielt das Sportlehrer*innenhandeln? - Grimminger-Seidensticker, Elke (sportunterricht)

Körperbild, Bewegung und Sport in der Wahrnehmung von Grundschulkindern. Ergebnisse einer explorativen lnterviewstudie - Grimminger-Seidensticker, Elke; Korte, J.; Möhwald, Aiko Julia (sportunterricht)

A 14-weeks intervention study on changing preservice teachers’ psychological perspectives related to teaching inclusively: Explicit and implicit attitude, self-efficacy, and stress perception towards inclusion - Grimminger-Seidensticker, Elke; Lautenbach, F.; Heyder, A.; Korte, J.; Möhwald, Aiko Julia (Frontiers in Education)

Quantitative and qualitative results of a body image pilot intervention in (pre)adolescent girls - Grimminger-Seidensticker, Elke; Korte, J. (Journal of Physical Education & Health)

Health concepts among socially disadvantaged children in France, Germany and Switzerland - Grimminger-Seidensticker, Elke; Aceti, Monica; Knobé, Sandrine; Vieille Marchiset, Gilles (Health Promotion International)
Summary As health concepts develop through exposure to, and experience with particular contexts, and as health concepts influence health behaviour, it is important for actors in health promotion programmes to understand an individual’s health concepts. This study focussed on health concepts among socially disadvantaged children in France, Germany, Italy and Switzerland—a hitherto less researched population group. We conducted focus groups with a total of 167 children aged 7–11 years (mean=8.76 years, SD=0.68). The aim of this study was to explore if the life situation across four different countries leads to similar health concepts, and how the particular, national health discourses are reflected in the children’s health concepts. The data were analysed through a structured qualitative content analysis and revealed four categories: ‘Symbols/symptoms of health/illness’, ‘Emotionality’, ‘Healthy/unhealthy practices’, and ‘Consequences of health problems’. The children’s health concepts are linked to concrete events and objects, and they are able to think in logical sequences. However, the children’s causal argumentation is uni-dimensional; they do not cover the complexity of the development of health problems. In particular, overweight stands for illness and is exclusively the result of unhealthy practices. In their concepts, the children reflect the national health promotion programme discourses about overweight. They seem to understand the messages of health education as ‘behaving well means being healthy’; however, such a health education message initiates accusations of ‘unhealthy persons’. In consequence, challenges for sensitive health education programmes (at school) are discussed.

A 14-Week Intervention Study on Changing Preservice Teachers’ Psychological Perspectives on Inclusion: Explicit and Implicit Attitudes, Self-Efficacy, and Stress Perception Toward Inclusion - Lautenbach, Franziska; Korte, Johanna; Möhwald, Aiko; Heyder, Anke; Grimminger-Seidensticker, Elke (Frontiers in Education)

SUBCLINICAL DISORDERED EATING AND BODY DISSATISFACTION IN NORMAL WEIGHT CHILDREN—THE ROLE OF PHYSICAL ACTIVITY AND MOTIVES TO EXERCISE - Grimminger-Seidensticker, Elke; Korte, Johanna; Möhwald, Aiko; Trojan, Jörg (Journal of Physical Education & Health)

Der Koran in seinem religions- und weltgeschichtlichen Kontext. Eschatologie und Apokalyptik in den mittelmekkanischen Suren - Ghaffar, Zishan

Der Koran in seinem religions- und weltgeschichtlichen Kontext. Eschatologie und Apokalyptik in den mittelmekkanischen Suren - Ghaffar, Zishan
Review von Holger Zellentin, Review of Qur'anic Research, Vol. 7 no. 5 (2021) Rezension von Bertram Schmitz, Theologische Literaturzeitung, Nr. 7, 2021, Spalte 657-658 Review von Sebastian Bitsch, Der Islam, Band 98, Heft 2, 2021, 591-598

Spectral Asymptotics for Kinetic Brownian Motion on Surfaces of Constant Curvature - Kolb, Martin; Weich, Tobias; Wolf, Lasse Lennart (arXiv:2011.06434)
The kinetic Brownian motion on the sphere bundle of a Riemannian manifold $M$ is a stochastic process that models a random perturbation of the geodesic flow. If $M$ is a orientable compact constantly curved surface, we show that in the limit of infinitely large perturbation the $L^2$-spectrum of the infinitesimal generator of a time rescaled version of the process converges to the Laplace spectrum of the base manifold.

Körperspannung trainieren : auf die richtige Spannung kommt es an - Körperspannung als zentrale Lernvoraussetzung im (Gerät-)TurnenKörperspannung trainieren: auf die richtige Spannung kommt es an - Körperspannung als zentrale Lernvoraussetzung im (Gerät-)Turnen - Dörrer, Hans-Joachim; Köster, Carolin (Sportpädagogik)

Language Teachers and Crowdsourcing - Arhar Holdt, Špela; Zanasi, Lorenzo; Weber, Tassja; Volodina, Elena; Rodosthenous, Christos; Ordulj, Antonia; Miloshevska, Lina; Lazić Konjik, Ivana; Koeva, Svetla; Kasperavičienė, Ramunė; Hatipoglu, Ciler; Fort, Karën; et al. (Rasprave Instituta za hrvatski jezik i jezikoslovlje)
The paper presents a cross-European survey on teachers and crowdsourcing. The survey examines how familiar language teachers are with the concept of crowdsourcing and addresses their attitude towards including crowdsourcing into language teaching activities. The survey was administrated via an online questionnaire and collected volunteers’ data on: (a) teachers’ experience with organizing crowdsourcing activities for students/pupils, (b) the development of crowdsourced resources and materials as well as (c) teachers’ motivation for participating in or employing crowdsourcing activities. The questionnaire was disseminated in over 30 European countries. The final sample comprises 1129 language teachers aged 20 to 65, mostly working at institutions of tertiary education. The data indicates that many participants are not familiar with the concept of crowdsourcing resulting in a low rate of crowdsourcing activities in the classroom. However, a high percentage of responding teachers is potentially willing to crowdsource teaching materials for the language(s) they teach. They are particularly willing to collaborate with other teachers in the creation of interactive digital learning materials, and to select, edit, and share language examples for exercises or tests. Since the inclusion of crowdsourcing activities in language teaching is still in its initial stage, steps for further research are highlighted.
Keywords: Linguistics and Language; Language and Linguistics

Präpositionen und Deutsch als Fremdsprache: Quantitative Fallstudien im Lernerkorpus MERLIN - Weber, Tassja
Die Dissertation beschäftigt sich mit dem Gebrauch von Präpositionen (z. B. an, für) und Präpositionalphrasen (z. B. an der Wand, für dich) durch Lernende des Deutschen als Fremdsprache (DaF). Es wird untersucht, welche ausgewählten Variablen den Gebrauch dieser Strukturen beeinflussen. Der Schwerpunkt liegt dabei auf Gebrauchsschwierigkeiten. Auf Basis lernersprachlicher Daten im digitalen, frei verfügbaren Lernerkorpus MERLIN (merlin-platform.eu) und unter Berücksichtigung grundlegender Annahmen aktueller Spracherwerbstheorien werden quantitativ ausgerichtete Fallstudien zu folgenden Einflussvariablen durchgeführt: Die Erstsprache der Lernenden, die Sprachkompetenz, die syntaktische Funktion der PP und der semantische Gehalt der Präposition. Die Arbeit bettet sich ein in die Lernerkorpusforschung an der Schnittstelle zur Zweit- und Fremdspracherwerbsforschung. Die Ergebnisse zeigen insgesamt für alle Einflussvariablen einen Effekt und bestätigen damit den Einfluss intralingualer sowie interlingualer Merkmale im Sprachgebrauch von Lernenden. Dabei wird deutlich, dass die Gebrauchsschwierigkeiten nicht quantitativer (Korrektheit), sondern eher qualitativer Natur (Fehlertypen) sind. Die Dissertation liefert empirisch fundierte Erkenntnisse zu Schwierigkeiten im Gebrauch von Präpositionen und PP durch DaF-Lernende, für die bisher systematische, korpusgestützte Untersuchungen fehlten. Die Arbeit zeigt dabei exemplarisch auf, wie Annahmen aus der Spracherwerbsforschung anhand von Lernerkorpusdaten überprüft und mögliche Einflussvariablen im Sprachgebrauch ermittelt werden können. Die Erkenntnisse sind auch für andere Forschungsfelder (u.a. Fremdsprachenunterricht und maschinelle Sprachverarbeitung) relevant.
Keywords: Deutsch als Fremdsprache; Korpuslinguistik; Lernerkorpora; Präpositionen; Präpositionalphrasen; Grammatik; Regressionsanalyse

Noether’s-type theorems on time scales - Anerot, Baptiste; Cresson, Jacky; Hariz Belgacem, Khaled; Pierret, Frederic (Journal of Mathematical Physics)
Keywords: Mathematical Physics; Statistical and Nonlinear Physics

Noether’s-type theorems on time scales - Anerot, Baptiste; Cresson, Jacky; Hariz Belgacem, Khaled; Pierret, Frederic (Journal of Mathematical Physics)
Keywords: Mathematical Physics; Statistical and Nonlinear Physics

CP2K: An electronic structure and molecular dynamics software package - Quickstep: Efficient and accurate electronic structure calculations - Kühne, Thomas; Iannuzzi, Marcella; Ben, Mauro Del; Rybkin, Vladimir V.; Seewald, Patrick; Stein, Frederick; Laino, Teodoro; Khaliullin, Rustam Z.; Schütt, Ole; Schiffmann, Florian; Golze, Dorothea; Wilhelm, Jan; et al. (The Journal of Chemical Physics)
CP2K is an open source electronic structure and molecular dynamics software package to perform atomistic simulations of solid-state, liquid, molecular, and biological systems. It is especially aimed at massively parallel and linear-scaling electronic structure methods and state-of-theart ab initio molecular dynamics simulations. Excellent performance for electronic structure calculations is achieved using novel algorithms implemented for modern high-performance computing systems. This review revisits the main capabilities of CP2K to perform efficient and accurate electronic structure simulations. The emphasis is put on density functional theory and multiple post–Hartree–Fock methods using the Gaussian and plane wave approach and its augmented all-electron extension.

A Submatrix-Based Method for Approximate Matrix Function Evaluation in the Quantum Chemistry Code CP2K - Lass, Michael; Schade, Robert; Kühne, Thomas; Plessl, Christian (Proc. International Conference for High Performance Computing, Networking, Storage and Analysis (SC))
Electronic structure calculations based on density-functional theory (DFT) represent a significant part of today's HPC workloads and pose high demands on high-performance computing resources. To perform these quantum-mechanical DFT calculations on complex large-scale systems, so-called linear scaling methods instead of conventional cubic scaling methods are required. In this work, we take up the idea of the submatrix method and apply it to the DFT computations in the software package CP2K. For that purpose, we transform the underlying numeric operations on distributed, large, sparse matrices into computations on local, much smaller and nearly dense matrices. This allows us to exploit the full floating-point performance of modern CPUs and to make use of dedicated accelerator hardware, where performance has been limited by memory bandwidth before. We demonstrate both functionality and performance of our implementation and show how it can be accelerated with GPUs and FPGAs.

Janus-type dual emission of a Cyclometalated Iron(III) complex - Bauer, Matthias; Steube, Jakob; Päpcke, Ayla; Bokareva, Olga; Reuter, Thomas; Demeshko, Serhiy; Schoch, Roland; Hohloch, Stephan; Meyer, Franc; Heinze, Katja; Kühn, Oliver; Lochbrunner, Stefan
Photoactive compounds are essential for photocatalytic and luminescent applications, such as photoredox catalysis or light emitting diodes. However, the substitution of noble metals, which are almost exclusively used, by base metals remains a major challenge on the way to a more sustainable world.1 Iron is a dream candidate for this ambitious aim.2 But compared to noble metal complexes that show long-lived metal-to-ligand charge-transfer (MLCT) states, realization of emissive and photoactive iron complexes is demanding, due to the fast deactivation of charge transfer states into non-emissive inactive states. No MLCT emission has been observed for monometallic iron complexes before. Consequently, dual emission could also not yet be realized with iron complexes, as it is a very rare property even of noble metal compounds. Here we report the Fe III complex [Fe(ImP) 2 ][PF 6 ] (HImP = 1,1’-(1,3-phenylene)bis(3-methyl-1-imidazol-2-ylidene)), showing Janus-type dual emission by combining LMCT (ligand-to-metal charge transfer) with MLCT luminescence. The respective excited states are characterized by a record lifetime of τ MLCT = 4.2 ns, and a moderate τ LMCT = 0.2 ns. Only two emissive Fe III compounds are known so far and they show LMCT luminescence only.3,4 The unique properties of the presented complex are caused by the specific ligand design combining four N-heterocyclic carbenes with two cyclometalating groups, using the σ-donor strength of six carbon atoms and the acceptor capabilities of the central phenyl rings. Spectroscopically, doublet manifolds could be identified in the deactivation process, while (TD)DFT analysis revealed the presence of quartets as well. With three key advancements of realizing the first iron complex showing dual luminescence, a MLCT luminescence and a world record MLCT lifetime, the results constitute a basis for future application of iron complexes as white light emitters and new photocatalytic reactions making use of the Janus-type properties of the developed complex.

Benchmarking the Lifecycle of Knowledge Graphs - Röder, Michael; Sherif, Mohamed; Saleem, Muhammad; Conrads, Felix; Ngonga Ngomo, Axel-Cyrille (Knowledge Graphs for eXplainable Artificial Intelligence: Foundations, Applications and Challenges)
Keywords: dice group_aksw roeder sherif saleem fconrads ngonga

Applying edge-counting semantic similarities to Link Discovery: Scalability and Accuracy - Georgala, Kleanthi; Röder, Michael; Sherif, Mohamed; Ngonga Ngomo, Axel-Cyrille (Proceedings of Ontology Matching Workshop 2020)
With the growth in number and variety of RDF datasets comes an in- creasing need for both scalable and accurate solutions to support link discovery at instance level within and across these datasets. In contrast to ontology matching, most linking frameworks rely solely on string similarities to this end. The limited use of semantic similarities when linking instances is partly due to the current literature stating that they (1) do not improve the F-measure of instance linking approaches and (2) are impractical to use because they lack time efficiency. We revisit the combination of string and semantic similarities for linking instances. Contrary to the literature, our results suggest that this combination can improve the F-measure achieved by instance linking systems when the combination of the measures is performed by a machine learning approach. To achieve this in- sight, we had to address the scalability of semantic similarities. We hence present a framework for the rapid computation of semantic similarities based on edge counting. This runtime improvement allowed us to run an evaluation of 5 bench- mark datasets. Our results suggest that combining string and semantic similarities can improve the F-measure by up to 6% absolute.
Keywords: 2020 dice simba sherif hecate ngonga knowgraphs sys:relevantFor:limboproject limboproject sys:relevantFor:infai sys:relevantFor:bis limes limbo opal roeder georgala

LIGON – Link Discovery with Noisy Oracles - Sherif, Mohamed; Dreßler}, Kevin; Ngonga Ngomo, Axel-Cyrille (Proceedings of Ontology Matching Workshop 2020)
Link discovery plays a key role in the integration and use of data across RDF knowledge graphs. Active learning approaches are a common family of solutions to address the problem of learning how to compute links from users. So far, only active learning from perfect oracles has been considered in the literature. However, real oracles are often far from perfect (e.g., in crowdsourcing). We hence study the problem of learning how to compute links across knowledge graphs from noisy oracles, i.e., oracles that are not guaranteed to return correct classification results. We present a novel approach for link discovery based on a probabilistic model, with which we estimate the joint odds of the oracles’ guesses. We combine this approach with an iterative learning approach based on refinements. The resulting method, Ligon, is evaluated on 10 benchmark datasets. Our results suggest that Ligon configured with 10 iterations and 10 training examples per iteration achieves more than 95% of the F-measure achieved by state-of-the-art algorithms trained with a perfect oracle. Moreover, Ligon outperforms batch learning approaches devised to be trained with small amounts of training data by more than 40% F-measure on average.
Keywords: 2020 dice simba sherif ligon ngonga knowgraphs sys:relevantFor:limboproject limboproject sys:relevantFor:infai sys:relevantFor:bis limes limbo opal kevin

Tentris – A Tensor-Based Triple Store - Bigerl, Alexander; Conrads, Felix; Behning, Charlotte; Sherif, Mohamed; Saleem, Muhammad; Ngonga Ngomo, Axel-Cyrille (The Semantic Web -- ISWC 2020)
Keywords: sys:relevantFor:infai sys:relevantFor:bis sys:relevantFor:simba sys:relevantFor:limbo sys:relevantFor:raki daikiri speaker tentris knowgraphs bigerl fconrads saleem sherif ngonga group_aksw dice

ProBERT: Product Data Classification with Fine-tuning BERT Model - Zahera, Hamada Mohamed Abdelsamee; Sherif, Mohamed (Proceedings of Mining the Web of HTML-embedded Product Data Workshop (MWPD2020))
Keywords: 2020 dice zahera sherif knowgraphs sys:relevantFor:limboproject limboproject sys:relevantFor:infai sys:relevantFor:bis limes limbo opal

LIGER – Link Discovery with Partial Recall - Georgala, Kleanthi; Sherif, Mohamed; Ngonga Ngomo, Axel-Cyrille (Proceedings of Ontology Matching Workshop 2020)
Modern data-driven frameworks often have to process large amounts of data periodically. Hence, they often operate under time or space constraints. This also holds for Linked Data-driven frameworks when processing RDF data, in particular, when they perform link discovery tasks. In this work, we present a novel approach for link discovery under constraints pertaining to the expected recall of a link discovery task. Given a link specification, the approach aims to find a subsumed link specification that achieves a lower run time than the input specification while abiding by a predefined constraint on the expected recall it has to achieve. Our approach, dubbed LIGER, combines downward refinement oper- ators with monotonicity assumptions to detect such specifications. We evaluate our approach on seven datasets. Our results suggest that the different implemen- tations of LIGER can detect subsumed specifications that abide by expected recall constraints efficiently, thus leading to significantly shorter overall run times than our baseline.
Keywords: 2020 dice simba sherif hecate ngonga knowgraphs sys:relevantFor:limboproject limboproject sys:relevantFor:infai sys:relevantFor:bis limes limbo opal georgala

„Wir müssen die Sorgen der Menschen ernst nehmen“ – Zur sprachlichen Thematisierung von Sorge und Angst in der Politik - Georgi, Christopher (Diskurs – ethisch)

Prudence and prevention: Empirical evidence - Mayrhofer, Thomas; Schmitz, Hendrik
Theoretical papers show that optimal prevention decisions in the sense of selfprotection (i.e., primary prevention) depend not only on the level of (second-order) risk aversion but also on higher-order risk preferences such as prudence (third-order risk aversion). We study empirically whether these theoretical results hold and whether prudent individuals show less preventive (self-protection) effort than non-prudent individuals. We use a unique dataset that combines data on higher-order risk preferences and various measures of observed real-world prevention behavior. We find that prudent individuals indeed invest less in self-protection as measured by influenza vaccination. This result is driven by high risk individuals such as individuals >60 years of age or chronically ill. We do not find a clear empirical relationship between riskpreferences and prevention in the sense of self-insurance (i.e. secondary prevention). Neither risk aversion nor prudence is related to cancer screenings such as mammograms, Pap smears or X-rays of the lung.
Keywords: prudence; risk preferences; prevention; vaccination; screening

Sprachsensible Formulierung von Erhebungsinstrumenten - Schwabl, Franziska; Janssen, Elmar; Sloane, Peter F. E. (Zeitschrift für Berufs- und Wirtschaftspädagogik)
Keywords: Applied Mathematics; General Mathematics

»auch auf gesanglichem Gebiete überaus thätig«. Max Reger und das Lied - Ried, Dennis (Musik in Baden-Württemberg. Jahrbuch 2019/20)

Do product testing programs lead to more favorable online reviews? (ausgezeichnet mit Best Paper Award) - Garnefeld, I.; Krah, T.; Böhm, Eva; Gremler, D. D. (2020 AMA Winter Academic Conference, San Diego, CA)

Manufacturers’ service growth through mergers and acquisitions – An event study - Eggert, A.; Böhm, Eva; Akalan, R.; Gebauer, H. (2020 AMA Winter Academic Conference, San Diego, CA)

Literarisches Wissen vom marxistischen Wissenschaftsbetrieb. Historiographische Ideologiedebatten in Gerti Tetzners „Karen W.“ - Elit, Stefan (Wirkendes Wort)

Dei ex machina: The Interaction Order of Gamified Distance Learning - Erofeeva, M.A.; Klowait, Nils (Sociology of Power)
The article analyzes the implementation of an online educational module and its impact on the organization of the classroom’s interaction order. The latter is institutionally constrained by the presence of a goal and the distribution of roles between teacher and students. The introduction of a digital learning platform adds a technological context to the institutional setting. The article considers technologies as possessing communicative affordances — opportunities for action made possible or delimited through their use. Technologies bring new interactive resources to the process of education and can affect the organization of the classroom’s interaction order. Using multimodal conversation analysis, we analyzed video recordings of the telemediated interaction of Russia-based students and teachers within a gamified online educational module. We investigate a case in which a student’s correct answer is nevertheless corrected by the teacher. We demonstrate that the teacher initiates the correction because they are guided by the ordering of the game elements within the interface. Based on a detailed analysis of the teacher’s mouse movement in relation to ongoing turns-at-talk, we show that this orientation is sustained by all participants. The work contributes to classroom interaction studies and affordance theory and develops the methodology of multimodal transcription for mediated contexts. The primary result of the study is an empirical demonstration that the relevance of technological affordances for interactants is situationally produced, and that this process is associated with the interweaving of the institutional and technical context of interaction. The conclusion discusses the relationship between affordances and institutional norms.

The Head-Fake Effect in Basketball Is Based on the Processing of Head Orientation, but Not on Gaze Direction - Weigelt, Matthias; Güldenpenning, Iris; Steggemann-Weinrich, Yvonne (Psychology)
Keywords: General Earth and Planetary Sciences; General Environmental Science

Electrify your Game! Anodal tDCS Increases the Resistance to Head Fakes in Basketball - Friehs, Maximilian A.; Güldenpenning, Iris; Frings, Christian; Weigelt, Matthias (Journal of Cognitive Enhancement)
Keywords: General Medicine

Drivers and outcomes of salespersons’ value opportunity recognition competence in solution selling - Böhm, Eva; Eggert, Andreas; Terho, Harri; Ulaga, Wolfgang; Haas, Alexander (Journal of Personal Selling and Sales Management)
Keywords: Management of Technology and Innovation; Human Factors and Ergonomics

Is the head-fake effect in basketball robust against practice? Analyses of trial-by-trial adaptations, frequency distributions, and mixture effects to evaluate effects of practice - Güldenpenning, Iris; Schütz, Christoph; Weigelt, Matthias; Kunde, Wilfried (Psychological Research)
Reactions to the pass of a basketball player performing a head fake are typically slower than reactions to a basketball player who passes without a head fake (i.e., head-fake effect). The present study shows that extensive practice reduces the head-fake effect in basketball. Additional analyses were conducted to explore the mechanism behind the reduced head-fake effect. First, we analyzed whether or not participants developed some control over the processing of irrelevant gaze direction, as indicated by specific trial-to-trial adaptations (i.e., congruency sequence effect). Second, we fitted the individual frequency distributions of RTs to ex-Gaussian distributions, to evaluate if practice specifically affects the Gaussian part of the distribution or the exponential part of the distribution. Third, we modeled individual RT distributions as the so-called mixture effects to examine whether the way irrelevant gaze direction impacts performance (either occasionally but massively or continuously but moderately) changes with practice. The analyses revealed that the effect of practice could not be explained with an increasing congruency-sequence effect. Also, it could not be found in the ex-Gaussian distributional analyses. The assumption that residual failure to inhibit the processing of the gaze direction in contrast to continuous failures to do so might favor mixed effects over uniform effects at later courses of practice could not be validated. The reduced head-fake effect thus is argued to source in participants’ general increasing ability to inhibit the processing of the task-irrelevant gaze direction information and/or in a priority shift of gaze processing to a processing of the pass direction.
Keywords: Arts and Humanities (miscellaneous); Developmental and Educational Psychology; Experimental and Cognitive Psychology; General Medicine

Social cues can impact complex behavior unconsciously - Schütz, Christoph; Güldenpenning, Iris; Koester, Dirk; Schack, Thomas (Scientific Reports)
Abstract In three experiments, we investigated the effect of unconscious social priming on human behavior in a choice reaction time task. Photographs of a basketball player passing a ball to the left/right were used as target stimuli. Participants had to respond to the pass direction either by a whole-body (complex) response or a button-press (simple) response. Visually masked stimuli, showing both a task-relevant cue (pass direction) and a task-irrelevant, social cue (gaze direction), were used as primes. Subliminal social priming was found for kinematic (center of pressure) and chronometric measures (response times): gaze direction in the primes affected responses to the pass direction in the targets. The social priming effect diminished when gaze information was unhelpful or even detrimental to the task. Social priming of a complex behavior does not require awareness or intentionality, indicating automatic processing. Nevertheless, it can be controlled by top-down, strategic processes.
Keywords: Multidisciplinary

Head-fake perception in basketball: the relative contributions of expertise, visual or motor training, and test repetition - Güldenpenning, Iris; Kunde, Wilfried; Weigelt, Matthias (International Journal of Sport and Exercise Psychology)
Keywords: Applied Psychology; Social Psychology

Processing deceptive information in sports: Individual differences for responding to head fakes depends on the attentional capability of the observer - Güldenpenning, Iris; Weigelt, Matthias; Memmert, Daniel; Klatt, Stefanie (Psychology of Sport and Exercise)
Keywords: Applied Psychology

Cognitive load reduces interference by head fakes in basketball - Güldenpenning, Iris; Kunde, Wilfried; Weigelt, Matthias (Acta Psychologica)
Keywords: Arts and Humanities (miscellaneous); Developmental and Educational Psychology; Experimental and Cognitive Psychology; General Medicine

Negotiating weights for burden sharing rules in international climate negotiations: an empirical analysis - Kesternich, Martin; Löschel, Andreas; Ziegler, Andreas (Environmental Economics and Policy Studies)
Abstract We have collected data from a world-wide survey among COP delegates to empirically investigate preferences for certain burden sharing rules among key groups in a setting that reflects the possibility of observing concessions from negotiating partners. In our survey, the participants had the opportunity to select and combine up to eight (pre-defined) burden sharing rules and to assign relative weights to the selected rules in their preferred bundle. We examine whether such a mechanism helps to overcome the currently strictly (self-interested) strategic claims on equity in the negotiation process. We observe that delegates from different groups of countries show a general willingness for concessions. However, the degree to which different burden sharing rules are taken into consideration partly differs between countries. As a key insight we report that the individual assessment of the polluter-pays rule based on current emissions does not only stress the persistence of the traditional Annex-B/Non-Annex-B division but also suggests tendencies for a more fragmented grouping with different positions between, for example, delegates from developing countries (i.e. G77 members) and emerging countries (i.e. BASIC). At the same time, we observe tendencies for a more harmonized view among key groups towards the ability-to-pay rule in a setting of weighted burden sharing rules.
Keywords: Management; Monitoring; Policy and Law; Economics and Econometrics

Electrify your game! Anodal tDCS increases the resistance to head fakes in basketball - Friehs, Maximilian A; Güldenpenning, Iris; Frings, Christian; Weigelt, Matthias (Journal of Cognitive Enhancement)

Valence-dependent changes of neural processing of augmented feedback after extensive practice of a new motor task - Margraf, Linda; Krause, Daniel; Weigelt, Matthias

Zwischen Trend und Tradition: die Vielfalt des klassischen Gerätturnens und der innovativen Formen des Sichbewegens im Sportunterricht ausgeglichen nutzen. - Köster, Carolin; Kehne, Miriam (Sportpädagogik)